(Des)cristalizações de estereótipos femininos nos comerciais de televisão da Skol de 2017 - Gomes, Cristiana Frazão (2020)
Recently, Discourse Analysis (DA) has developed certain relations with other areas of knowledge - that is to say, different from that “amalgam” DA was constituted as a discipline - such as, social communication or cognition. Such relations have been promoting displacement of its theoretical framework or enriching the analytical categories with which one could operate. We propose on this work, based on a research clipping, to test the productivity of Marie-Anne Paveau's recent proposal, specifically from the theoretical articulation supported by her in two of her recent publications, namely: Os pré-discursos: sentido, memória e cognição (2013) e Linguagem e moral (2015)1 . In these works, the author's objective is to articulate discourse and cognition that, it seems to her, can “enrich and perhaps renew the practices of analysis that perhaps begin to exhaust its possibilities” (PAVEAU, 2013a, p. 9). Based on Paveau's considerations, our corpus initially constitutes the Skol Beer Brand’s Carnival Campaign, that it can be considered as a moral discursive event, that is, it is a campaign around which it is possible to identify, in the environment, a set of metadiscourses that point to possible faults. Then, efforts were directed to the analysis of three films produced in 2017, that materialize the discursive change of the Beer Brand. The present work aims, therefore, to describe the functioning of representations in advertising discourse and female stereotypes present in SKOL'sspeeches considered from categoriessuch as pre-speeches, which refersto a framework of beliefs, values and knowledge that has an instructional function for the production of speeches. Therefore, this work also focuses, therefore, on the pre-speeches that, in some way, are likely to recover in such advertisements with regard to the representation of the female in this type of advertising and the moral discursive event, the in order, still, to confirm that, in fact, there is a displacement of the stereotypes circulated in this universe. Thus, the hypotheses raised were confirmed in this research, that is, there is in fact a movement in progress in order to de-crystallize female stereotypes circulating in the advertising universe and this is, to a certain extent, linked to a greater concern of discursive decency by part of some companies, considering the socio-historical-cultural moment that the world is going through. This displacement - which is not only national but has an international scope - despite being slow is already striking and visible and has generated a slight discomfort on the part of other subjects who possibly disagree.